Routledge handbook of Southeast Asian politics - Robison, Richard 1943- (Routledge, 2014)
"This handbook provides a comprehensive analysis of the major themes that have defined the politics of Southeast Asia. It provides a comprehensive and cutting-edge examination of this important subject. The introductory chapter provides an overview of the theoretical and ideological themes that have dominated the study of the region's politics and presents the different ways the complex politics of the region have been understood. The contributions by leading scholars in the field cover a range of broad questions about the dynamics of politics. The handbook analyses how the dominant political and social coalitions of the region were forged in the Cold War era, and assesses the complex processes of transition towards various forms of democratic politics. How institutions and systems of governance are being forged in an increasingly global environment is discussed and whether civil society in Southeast Asia has really evolved as an independent sphere of social and political activity. The handbook examines how national governments are dealing with growing tensions within the region as matters such as labour, human rights and the environment spill beyond national boundaries, and how they are establishing a place in the new global framework. By engaging the Southeast Asian experience more firmly with larger debates about modern political systems, the handbook is an essential reference tool for students and scholars of political science and Southeast Asian studies."--Publisher's description.